Mpox on Reddit: a Thematic Analysis of Online Posts on Mpox on a Social Media Platform among Key Populations. - Hong, Chenglin (Journal of Urban Health, 2023)
The 2022–2023 mpox outbreak has disproportionately impacted gay, bisexual, and other men who have sex with men (GBMSM). The US CDC recommended individuals to explore safer sexual practices that minimize the potential risk of exposure and also strongly encouraged for eligible individuals to prioritize vaccination. This study aimed to analyze social media data related to mpox on Reddit since the mpox outbreak and identify themes associated with the impact on social behaviors and social processes among targeted population. Publicly available data were collected from the social media Reddit. We extracted the summarized mpox-related posts since the beginning of May 2022 from popular subreddits that were popular among GBMSM. We thematically analyzed the content to identify the overall themes related to the GBMSM's responses to the outbreak. There is an overall increase in the number of daily mpox-related posts, with three upticks in late May, late July, and early August 2022, which may correspond to the dates that the first mpox case was identified in the USA, the WHO declared a global public health emergency, and the US Department of Health and Human Services declared a public health emergency. Four themes were identified: (1) changes in sexual behaviors and social activities; (2) mpox vaccine attitude, uptake, and hesitancy; (3) perceived and experienced stigma and homophobia, and mental distress; and (4) online information-seeking and mutual aid and support. GBMSM changed their sexual behaviors and social activities to mitigate their exposure to the virus during this outbreak and actively sought and shared information about mpox vaccination in their respective settings, while some were hesitant due to concerns about side effects and potential effectiveness. Perceived and experienced stigma and discrimination on gay- and same sex-identify have impacted GBMSM's mental health. Interventions to promote the mpox vaccine must address the historical medical mistrust and vaccine hesitancy among GBMSM.